A legal analysis on sexual orientation in Malaysia / Nurul Ashiqin Shamsuri, Sheena Hasanah Abdul Hadi and Zuriatul Mida Nor Azmi - Shamsuri, Nurul Ashiqin; Abdul Hadi, Sheena Hasanah; Nor Azmi, Zuriatul Mida (2005)
This research entitled "A Legal Analysis on Sexual Orientation Discrimination in Malaysia" mainly discusses on the issue of homosexuality in the perspective of this country. The purpose of this research is to identify the problem faced by those who involved in homosexuality and how the laws in Malaysia deal with all the problems. The definition and detailed view of homosexuality are thoroughly explained in Chapter 1. Meanwhile, the Second Chapter deals with all the relevant Civil Laws available in Malaysia, which directly or indirectly affects homosexual citizens. The study in this area will expose the loopholes that exist in Malaysia Legal System. In the Third Chapter, on the other hand, deals with Criminal Laws that criminalize homosexual acts in this country. There are two main sections that deal with this issue that is Malaysian Penal Code and the second one is the provision of Shariah Law of the Federal Territories. Here, the highlighted case in this chapter is the case of PP v Dato' Seri Anwar Ibrahim. In addition the Fourth Chapter discusses on Comparative Study. This chapter shall examine related legislations affecting homosexuals in the United States, other Islamic countries and other Non-Muslim Countries. This Comparative study is vital as it allows Malaysians to compare their local laws with that of other countries. Lastly is the most important part, which is inclusive of the conclusion and recommendations. This is discussed on the last chapter that is Chapter 5.